The Representation of Argumentative Discourse in Doha Debates - Mariana, Sitti Dina; gultom, Eva (PT. PENERBIT TIGA MUTIARA, 2023)
The study aims to analyze the argumentative process contained in the YouTube Channel Doha Debate with the title “Gender Equality (Full Debate) Doha debates presenting three spokespersons by using five principles based on Damer’s theory. The method used in this study is qualitative descriptive. Data has been collected in the analysis by way of presenting, describing, and interpreting data. Research results show that there are twelve data in in this study, such as structural principle (twelve data), relevance (ten data), acceptability (one Data), sufficiency (six data), and rebuttal principle (four data). The researcher found that the structural principle is most dominantly used in the argument because there is a claim from the speaker’s argument to strengthen the speaker’s statement so that it can be accepted by the audience, relevance of reasons that are directly related to the claim, acceptability of the audience's opinion regarding the speakers’ argument, sufficiency provides evidence to strengthen the argument, and rebuttal principle which is the speaker's criticism of the argument presented by the opponent. Therefore, this concluded that the most consistent during the debate was Randa saying that quotas can help gender equality while Christina said that quotas cannot work and only harm because there is no evidence that gender quotas can help equality.